Prostorne prepreke - prilagodbe i rješenja - Barić, Asja; Dolanc, Ivan; Haničar, Elizabeta Pavlović, Nataša; Španić, Damir Udiljak-Bugarinovski, Zrinka (2012)
Autori govore o prilagodbama prostora studntima s invaliditetom.
HRV